PENYELIDIKAN TINGKAT PENGARUH PATAHAN GEOLOGI DENGAN ARAH RETAKAN DI JALAN RAYA: STUDI KASUS JALAN BESAR DI BALIKPAPAN - Abdi Suprayitno; Amiruddin Amiruddin; Andrea Talaiftha; Reza Nur Maulidya (PETROGAS: Journal of Energy and Technology, 2020)
Damage to roads in the Balikpapan area is a problem that recurs every year. The patchwork project is a scene in itself at the locations where roads are damaged. The causes of road damage have long been studied by researchers from the civilian field. Research related to the road structure and the underlying rock engineering conditions has been carried out. The purpose of this research is to prove that apart from the influence of the characteristics of the road structure and its rocks, the effect of geological fractures can also be considered. This study uses the main data to measure the direction of the road cracks and the direction of the geological fault. The data is then analyzed how far it affects one another. Based on the measurement data of the direction of the cracks on the highway and the drawing of geological structure straightness through satellite images which are then compared, the results show that there are similarities in the direction of the cracks and the geological structure in Balikpapan. These directions are Northwest - West - Southwest with Southeast-East-Northeast. Therefore, it can be concluded that the effect of cracks on the road has a direct influence on the geological structure in Balikpapan.